Lymphangioleiomyomatosis - Anderluh, Franc (Radiology and oncology (Ljubljana), 2002)
Background. Lymphangioleiomyomatosis is a rare disease of unknown origin, which affects women in their reproductive period. It is characterised by non-neoplastic proliferation of atypical smooth muscle cells in the lung parenchyma, lymphatic vessels and mediastinal and abdominal lymph nodes. The most common presenting symptoms are spontaneous pneumothorax, dyspnea, hemoptysis and chylothorax. Conclusions. High-resolution computed tomography (HRCT) and open lung biopsy followed by the immunohistologic studies are two diagnostic procedures with which diagnosis can be confirmed. Various treatmentmodalities are applied, particularly hormonal therapy, though their efficacy remain unknown. The prognosis of patients is bad.
Keywords: Biopsija; Biopsy; Diagnosis; diagnostika; Limfangiomiomatoza; limfni sistem; Lymphangiomyomatosis; Pathology; pljuča; Therapy; Tomografija radiografska, računalniška; Tomography, X-ray computed